Characteristics and therapeutic potential of sodium-dependent phosphate cotransporters in relation to idiopathic basal ganglia calcification - Masatoshi Inden; Hisaka Kurita; Isao Hozumi (Elsevier, 2022)
Type-III sodium-dependent phosphate transporters 1 and 2 (PiT 1 and PiT 2, respectively) are proteins encoded by SLC20A1 and SLC20A2, respectively. The ubiquitous distribution of SLC20A1 and SLC20A2 mRNAs in mammalian tissues supports the housekeeping maintenance and homeostasis of intracellular inorganic phosphate (Pi), which is absorbed from interstitial fluid for normal cellular functions. SLC20A2 variants have been found in patients with idiopathic basal ganglia calcification (IBGC), also known as Fahr's disease or primary familial brain calcification (PFBC). Thus, disrupted Pi homeostasis is considered one of the major factors in the pathogenic mechanism of IBGC. In this paper, among the causative genes of IBGC, we focused specifically on PiT2, and its potential for a therapeutic target of IBGC.